Th17/Treg homeostasis, but not Th1/Th2 homeostasis, is implicated in exacerbation of human bronchial asthma - Zou, Xiao-ling (Ther Clin Risk Manag, 2018)
BACKGROUND: Th17 and regulatory T cell (Treg) play crucial roles in the pathogenesis of asthma. However, the association between Th17/Treg homeostasis and asthma exacerbation remains unclear. PATIENTS AND METHODS: To investigate the role of Th17/Treg bias in asthma exacerbation, 49 asthma patients were enrolled in the current study, of whom 31 had acute asthma exacerbation (exacerbation group) and 18 did not (non-exacerbation group). Meanwhile, 17 healthy subjects were recruited as normal controls (control group). By measuring interleukin (IL)-4, IL-13, interferon (IFN)-γ, IL-10, and IL-17A levels in plasma using enzyme-linked immunosorbent assay (ELISA) and determining the mRNA expression of T-bet, GATA-3, forkhead/winged helix transcription factor (Foxp3), and receptor-related orphan receptor γt (RORγt) in peripheral blood mononuclear cells (PBMCs) by quantitative real-time PCR. RESULTS: We found that IL-17A/IL-10 and RORγt/Foxp3 ratios were significantly increased in the exacerbation group compared with that in the non-exacerbation group, while IL-4/IFN-γ and GATA-3/T-bet ratios remained unchanged. Moreover, IL-17A/IL-10 and RORγt/Foxp3 ratios, but not IL-4/IFN-γ or GATA-3/T-bet ratios, negatively correlated with forced expiratory volume in the first second (FEV(1))/FEV(1pred) and Asthma Control Test Questionnaire (ACT) scores in both exacerbation group and non-exacerbation group. In contrast, the IL-4/IFN-γ ratio was negatively correlated with FEV(1)/FEV(1pred) and ACT scores only in the non-exacerbation group but not in the exacerbation group, while the ratio of GATA-3/T-bet was correlated with neither FEV(1)/FEV(1pred) nor ACT scores in both groups with asthma. CONCLUSION: Our results suggest that the homeostasis of the Treg and Th17 cells is broken in asthma exacerbation and correlates with asthma severity and disease control status. The outcome has significant implication in understanding the progression of asthma and providing helpful information for physicians in the diagnosis and treatment of asthma patients.